UMP squash reservation system using lighting control - Mahdi Hishamuddin, Abdul Aziz (2016)
University Malaysia Pahang (UMP) sports center is the main place for students and staff doing their activities, such as playing squash, badminton, football and etc. Unfortunately, the manual reservation form using have many vulnerabilities. Some of the vulnerabilities are the staff need to write and print manual reservation form every day. Moreover, a customer using squash games without doing any reservation and payment. Next the customer will extend the games until the next customer comes in. This issue occurs because lack of surveillance from the staff to monitor the court or to turn off the light. Therefore, the UMP Squash Reservation System using Lighting Control was developed to overcome these problems. These system used agile: scrum as its project methodology. The outcome of UMP squash Reservation System using Lighting Control help UMP sports center staff to manage reservation and implement control over courts usage.